Usefulness of Indian Diabetes Risk Score in Predicting Treatment-Induced Hyperglycemia in Women Undergoing Adjuvant Chemotherapy for Breast Cancer - Prasad, Krishna; Hegde, Sanath; Rao, Suresh; D'souza, Rhea Katherine; George, Thomas; Suresh, Sucharitha; Baliga, Manjeshwar Shrinath (South Asian Journal of Cancer, 2023)
In the curative treatment of cancer with adjuvant chemotherapy, antineoplastic drugs, along with glucocorticoids, can induce hyperglycemia. The objective of this study was to assess the utility of the Indian Diabetes Risk Score (IDRS) in predicting treatment-induced hyperglycemia in women who were nondiabetic and normoglycemic at the start of chemotherapy. This prospective study was conducted with nondiabetic women who required adjuvant chemotherapy. Participants voluntarily completed the IDRS, providing information on age, waist circumference, family history of diabetes, and physical activity. Chemotherapy-induced hyperglycemia was defined as fasting blood glucose levels ≥100 mg/dL or random blood glucose levels ≥140 mg/dL during treatment. Data were categorized into women who developed hyperglycemia and those who remained normoglycemic during treatment and were analyzed using Fisher's exact test. A significance level of p < 0.05 was applied. Receiver operating characteristic (ROC) curves were constructed to validate the IDRS for predicting hyperglycemia. A total of 208 women met the inclusion criteria and participated in the study. The results revealed that 38.93% (81/208) developed hyperglycemia by the end of chemotherapy, as observed during their first follow-up after treatment. Fisher's exact test demonstrated a significant difference in the total IDRS score and its domains, including family history, physical activity, and waist circumference (p = 0.017–< 0.001), but not age. ROC analysis indicated that an IDRS score above 60 increased the likelihood of developing hyperglycemia, with a sensitivity of 81.3%, specificity of 54.7%, and an area under the curve of 0.727. These findings suggest that the IDRS is a sensitive tool for predicting adjuvant chemotherapy-induced hyperglycemia in breast cancer patients without diabetes. To the best of the authors' knowledge, this is the first study to evaluate the utility of the IDRS in predicting treatment-induced hyperglycemia in women undergoing adjuvant chemotherapy for breast cancer. Ongoing efforts are focused on understanding the underlying mechanisms and strategies for mitigation.
Keywords: Breast Cancer; adjuvant chemotherapy; hyperglycemia; Indian Diabetes Risk Score; diabetes